Pedagogical relationship: Max van Manen’s Pedagogy in the sources of educational experience - Ayala Carabajo, Raquel (Revista Complutense de Educación, 2017)
This article is about some of the fundamental meanings of Max van Manen’s Phenomenological Pedagogy. Van Manen’s pedagogy is little known in the Hispanic context, unlike what happens in other geographical contexts. It is indeed much less known than the phenomenological-hermeneutical methodology developed by the author, which is followed within empirical research in many different sciences. Thanks the hermeneutical phenomenological methodology, van Manen’s pedagogy explores and describes the essential structures of the educational experience from the existential or lived point of view. Thus, throughout his many studies, van Manen provides a deep and unique understanding of the pedagogical life basically discovered and described through structures or essential issues. This paper does not study his method but the nature and conditions of the pedagogical relation as a sample and selection of this wealth of phenomenological meaning. This issue contributes to the learning and practice of pedagogy as a deep, rich and unspeakable human experience, which possesses unavoidable ethical demands.
Keywords: Pedagogical Theory; Phenomenological Pedagogy; Pedagogical relation; teaching experience; applied phenomenology; van Manen